(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This study determined the effect of organizational culture and leadership style in school principals on improving teacherâ€™s performance in Muara Padang. This research used quantitative methods with correlational type. The study population was 60 people. The research sample was 51 people, where the sampling technique using a method developed by Isaac and Michael with an error rate of 5%. The results showed: 1) there was a positive and significant influence of organizational culture on teacherâ€™s performance; 2) there is a positive and significant influence between the principal’s leadership style and the teacher’s performance; 3) there is a simultaneous influence between organizational culture and school principal leadership style on teacherâ€™s performance in Muara Padang.